Nanocrystal, phase transformation and microstructure of Ni50Ti50 shape memory alloy (Mongolian Journal of Agricultural Sciences, 2018)
The nanocrystal, phase transformation and microstructure behavior of Ni50Ti50 shape memory alloy was investigated by scanning electronic microscope, X-ray diffraction and differential scanning calorimetry. The results showed that the microstructure of Ni-Ti binary alloy consists of the NiTi2 phase and the NiTi matrix phase. One-step phase transformation was observed alloy.